Trauma-Informed Care in an 8-Year-Old With Neurodivergence and Childhood Adversity: Clinical Reflections and the Impact of Secondary Trauma in CAMHS - Yasir Mateen; Mariam Khurshid (BJPsych Open)
Aims: Children with neurodevelopmental conditions, particularly ADHD, often face heightened vulnerability to adverse childhood experiences (ACEs), shaping their mental health trajectories. Trauma-informed care (TIC) provides a structured framework for understanding and addressing these vulnerabilities within clinical practice. Additionally, working with trauma-exposed children places significant psychological demands on mental health professionals, contributing to secondary traumatic stress (STS) and burnout. This study presents a complex case from CAMHS, illustrating the intersection of ADHD, trauma, and systemic care challenges, alongside an exploration of clinician well-being within trauma-intensive settings.